A Review of the Blue Economy: Improving Community Welfare with Innovation and Environmentally Friendly Technology - Hasanah Nur Uswatun; Wiranatakusuma Dimas Bagus; Aprizal Anggi (BIO Web of Conferences)
The study analyzed 58 articles from leading international journals from 2015 to 2024. The research found significant trends, such as more publications appearing in 2023, indicating a growing interest in sustainable economic practices. The research exhibited that the United States led the way in contributions, followed by China, the UK, Spain, and Australia, each of which demonstrated an essential role in the advancement of blue technologies. Key research areas include “Blue Economy,” “Innovation,” “Sustainable Development,” “Environmental Economics,” “Climate Change,” and “Sustainability.” All these fields display a strong desire to combine economic activity with consideration of environmental aspects. Notably, much of the research was conducted by smaller institutions, which emphasizes extensive field cooperation. New themes, such as “Blue Taxation,” “Blue Digital Value Co-Creation,” and “Blue Digital Finance,” are attracting increasing attention, showing creative ways and technological advances to support sustainability. This study suggests conducting research involving multiple disciplines, studying creative financing methods, maintaining policy stability, addressing socio- economic disparities, utilizing technology and innovation, and cooperating with people around the world. The purpose of these insights is to aid future research and practice, foster advances in technology and innovation in the Blue Economy, and ensure economic growth in harmony with environmental sustainability.